Zygomaticomaxillary modifications in the horizontal plane induced by micro-implant-supported skeletal expander, analyzed with CBCT images - Daniele Cantarella; Ramon Dominguez-Mompell; Christoph Moschik; Luca Sfogliano; Islam Elkenawy; Hsin Chuan Pan; Sanjay M. Mallya; Won Moon (SpringerOpen, 2018)
Abstract Background Miniscrew-assisted rapid palatal expansion (MARPE) has been adopted in recent years to expand the maxilla in late adolescence and adult patients. Maxillary Skeletal Expander (MSE) is a device that exploits the principles of skeletal anchorage to transmit the expansion force directly to the maxillary bony structures and is characterized by the miniscrews' engagement of the palatal and nasal cortical bone layers. In the literature, it has been reported that the zygomatic buttress is a major constraint that hampers the lateral movement of maxilla, since maxilla is located medially to the zygomatic arches. The objective of the present study is to analyze the changes in the zygomatic bone, maxillary bone, and zygomatic arches and to localize the center of rotation for the zygomaticomaxillary complex in the horizontal plane after treatment with MSE, using high-resolution cone-beam computed tomography (CBCT) images. Methods Fifteen subjects with a mean age of 17.2 (± 4.2) years were treated with MSE. CBCT records were taken before and after miniscrew-assisted maxillary expansion; three linear and four angular parameters were identified in the axial zygomatic section (AZS) and were compared from pre-treatment to post-treatment using the Wilcoxon signed rank test. Results Anterior inter-maxillary distance increased by 2.8 mm, posterior inter-zygomatic distance by 2.4 mm, angle of the zygomatic process of the temporal bone by 1.7° and 2.1° (right and left side) (P < 0.01). Changes in posterior inter-temporal distance and zygomaticotemporal angle were negligible (P > 0.05). Conclusions In the horizontal plane, the maxillary and zygomatic bones and the whole zygomatic arch were significantly displaced in a lateral direction after treatment with MSE. The center of rotation for the zygomaticomaxillary complex was located near the proximal portion of the zygomatic process of the temporal bone, more posteriorly and more laterally than what has been reported in the literature for tooth-borne expanders. Bone bending takes place in the zygomatic process of the temporal bone during miniscrew-supported maxillary expansion.